Electronic Gatekeeping: How Iowa Extension Home and Family News Releases are Affected by Electronic Distribution - Barbara A. Abbott (Journal of Applied Communications, 1986)
Computer technology is rapidly arriving in the offices of institutional news sources, allowing them to transmit their information electronically.